Kde sa stratil Boh-Štefan Hríb sa pýta troch pozoruhodných kňazov - Marek Orko Vácha . Karel Satoria . Tomáš Halík - Vácha, Marek Orko; Hríb, Štefan; Satoria, Karel; Halík, Tomáš (W Press, 2017)
de sa stratil Boh